A CONTENT ANALYSIS OF ENGLISH TEXTBOOK ‘BRIGHT’ FOR THE SECOND GRADERS OF JUNIOR HIGH SCHOOL BASED ON CURRICULUM 2013: ANALISIS ISI BUKU TEKS BAHASA INGGRIS ‘CERAH’ UNTUK SISWA KELAS II SMP BERDASARKAN KURIKULUM 2013 - Novi Dwi Maria Ulfa; Joko Wibowo (IAI Al-Qolam, 2021)
The aim of study is to measure and make sure what the content of English Textbook â€˜Brightâ€™ in The Second Graders of junior High School fulfills guidelines of Curriculum 2013, if there is any lack of needed content. This study uses Qualitative method specifically analysis descriptive. The study instrument is the writer herself and the data are collected from English textbook â€˜Brightâ€™ for the second graders of Junior High School and document of Curriculum 2013. The result of this study shows that only 73.9% materials in English textbook â€˜Brightâ€™ fulfill the feasibility of content requirement. 71 categories out of 96 obtain the score 4, 2 categories obtain score 2 and 23 categories obtain score 1. Which means in textbook, 73,9% of material on â€œBrightâ€ textbook are still acceptable and appropriate textbook in using that but need more consideration in using. The consideration is dominated in the diversity insight. Based on the strength and weakness of the textbook teacher can be more selective in using textbook suitable with the necessaryâ€™s students. Keywords: Content Analysis, English Textbook, The Second Graders Junior High School, Curriculum 2013